2017
DOI: 10.1007/s10295-016-1897-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Talaromyces thermophilus lipase gene in Trichoderma reesei by homologous recombination at the cbh1 locus

Abstract: CBH1 (cellobiohydrolase) comprises the majority of secreted proteins by Trichoderma reesei. For expression of Talaromyces thermophilus lipase gene in T. reesei, a self-designed CBH1 promoter was applied to drive the lipase gene expression cassette which was bracketed by flanking sequences of cbh1 gene for homologous recombination. Protoplast and Agrobacterium-mediated plasmid transformations were performed and compared, resultantly, transformation mediated by Agrobacterium was overall proved to be more efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…RSJ-1, B. thermoleovorans ID-1, Bacillus LBN2, Cohnella sp. A01, B. licheniformis Ht7, and B. sonorensis 4R which were 67.0 kDa, 60.0 kDa, 59.0 kDa, 57.0 kDa, 50.0 kDa, 45.0 kDa, 40.0 kDa, 39.0 kDa, 37 kDa, 34.0 kDa, 33.0 kDa, 29.5 kDa, 22.0 kDa, and 21.87 kDa, respectively, as determined using sodium dodecyl sulfate- (SDS-) polyacrylamide gel electrophoresis (PAGE) [ 4 , 9 , 11 , 18 , 23 , 26 , 27 , 29 – 33 , 54 , 69 71 ].…”
Section: Characteristics Of Ta Lipasesmentioning
confidence: 99%
“…RSJ-1, B. thermoleovorans ID-1, Bacillus LBN2, Cohnella sp. A01, B. licheniformis Ht7, and B. sonorensis 4R which were 67.0 kDa, 60.0 kDa, 59.0 kDa, 57.0 kDa, 50.0 kDa, 45.0 kDa, 40.0 kDa, 39.0 kDa, 37 kDa, 34.0 kDa, 33.0 kDa, 29.5 kDa, 22.0 kDa, and 21.87 kDa, respectively, as determined using sodium dodecyl sulfate- (SDS-) polyacrylamide gel electrophoresis (PAGE) [ 4 , 9 , 11 , 18 , 23 , 26 , 27 , 29 – 33 , 54 , 69 71 ].…”
Section: Characteristics Of Ta Lipasesmentioning
confidence: 99%
“…Lack of a generous cell wall facilitating DNA transfer makes filamentous fungi difficult to use in transformation experiments [49]. Owing to the complex processes involved in protoplast fusion, a research group found A. tumefaciens AGL1 to be efficient for the transformation of T-DNA to the host through a co-cultivation method and AS amendment [50]. Here, we applied the same method to transform the vp1 gene from A. tumefaciens AGL1 to T. reesei Rut-C30 with an efficiency of 250 to 400 successful transformants per 1 × 10 7 conidia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this heterologous lipase is very promising for industrial applications like paper making and detergent addition (68). On the other hand the synergetic degradation of cellulose and lipase makes this modified microorganism an excellent candidate to the treatment of oil-rich mill waste treatment, where the cellulose and triglycerides coexist (69)(70).…”
Section: New Cell Factories Producing Recombinant Lipasesmentioning
confidence: 99%